Horta escolar: uma UEPS para o ensino de ácidos, bases e pH - Silva, Claysson Xavier da (2021)
Teaching chemistry requires teachers to use different strategies to contextualize contents and promote students' critical thinking about the world around them. From this perspective, the topic of school garden raises the students' interest and can integrate meaningful learning of chemistry content with the students' daily lives. Thus, our research goal was to develop an educational product focused on the school garden topic for the teaching of acids, bases, and pH, and subject it for evaluation by chemistry teachers. The educational product is based on the Meaningful Learning Theory (MLT) and is aimed at chemistry teachers, including diversified activities, such as a theoretical deepening, suggested classroom activities, and experimental exercises involving physical and chemical soil analysis (videos of the experiments and the scripts in printable format are available in QR Code). The educational product was evaluated by four high school chemistry teachers from different public educational institutions. The research was qualitative and without the researcher’s intervention. Data collection instrument was an open-ended questionnaire, allowing the participants to express their opinions on the matters. The analysis of the results demonstrates that the educational product has accessible language, adequate layout and can contribute to the meaningful learning of the concepts of acids, bases, and pH.